Penerapan Hukum Bisnis Dalam Menjamin Kepatuhan Terhadap Etika Perusahaan di Era Digital - Cahyani, Ririn Dwi; Muzagi, Intan Nuraini; Sarpini, Sarpini (FEB Universitas Maritim Semarang, 2024)
Companies face new challenges in maintaining compliance with business ethics in the digital era which is characterized by technological advancements and globalization. It is essential to implement business laws to ensure that the company's practices not only comply with applicable regulations but also follow high moral standards. The study looks at how business law can help with ethical compliance in the digital environment, including data protection, transparency, and social responsibility. Using case studies from various industries, this study shows that consistent application of business laws and ongoing ethical counseling can create a strong culture of compliance. As a result, the company can not only reduce legal risks but also build a good reputation in the eyes of the public and consumers.